Influence of absorbed energy distribution along beam radius on ignition threshold of condensed explosives; IOP Conference Series: Materials Science and Engineering; Vol. 81 : Radiation-Thermal Effects and Processes in Inorganic Materials - Khaneft A. V. Aleksandr Villivich (2015, 2015)
Title screen